PENENTUAN PENGURANGAN KADAR FORMALIN PADA IKAN ASIN SEPAT DENGAN PERENDAMAN PERASAN BELIMBING WULUH DAN VARIASI SUHU AKUADES - Afdhil Arel; B.A. Martinus; Halimatun Sya’diyah (Universitas Wahid Hasyim Semarang, 2017)
ABSTRACT This research was conducted with the aim to determine the effect of soaking with starfruit (Averrhoa bilimbi L) and the effect of soaking with variations in water temperature to reducing levels of formaldehyde the salted fish. Research using Spektroquant NOVA 400 on wavelength 565 nm and using reagent HCHO-1 and HCHO-2 to know levels of formaldehyde in the salted fish. The results showedpercentage levels of formaldehydewithout soaking is 0%, while soaking with cold water (28ºC - 29ºC) is 31,62%, soaking with warm water (50ºC - 60ºC) is 53,69%, soaking with hot water (98ºC - 99ºC) is 62,78%, while soaking with starfruit konsentration 100% is 94,47%. This shows the soaking with water can reduce levels of formaldehyde highest with hot water, but soaking with starfruit konsentration 100% can reduce levels of formaldehyde higher of the soaking with hot water. Statistical calculation results with one-way ANOVA (p<0,05) gives results significantly differentbetween each treatment. Keywords : Formaldehyde, Starfruit (Averrhoa bilimbi L), Salted Fish, Spektroquan NOVA 400